2020
DOI: 10.1001/jamanetworkopen.2020.20802
|View full text |Cite
|
Sign up to set email alerts
|

Association of Violence Against Female Sex Workers Who Use Drugs With Nonfatal Drug Overdose in Kazakhstan

Abstract: IMPORTANCE Female sex workers (FSWs) who use drugs face increased risk of intimate partner violence (IPV) and nonpartner violence (NPV). The association between violence and drug overdose is unknown. OBJECTIVE To examine the association between IPV, NPV, and nonfatal drug overdose among FSWs who use drugs in Kazakhstan. DESIGN, SETTING, AND PARTICIPANTS This cross-sectional study included 400 adult FSWs in Kazakhstan who reported illicit drug use in the past year, exchanged sex for money or drugs, and reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…Findings showed that PWUIOs who were female were more likely to experience non-fatal overdose. According to previous studies, high rates of overdose among women have been reported, with 37.5% reporting a lifetime overdose and 18% reporting an overdose in the past three months, with most overdoses related to heroin or nonmedical use of prescription opioids (El-Bassel et al, 2020;Goldenberg, 2020). Although opioid-related overdoses is a major public health problem and may affect many groups of individuals, current knowledge of gendered experiences and requirements in the context of drug overdoses are arguably inadequate (Collins et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Findings showed that PWUIOs who were female were more likely to experience non-fatal overdose. According to previous studies, high rates of overdose among women have been reported, with 37.5% reporting a lifetime overdose and 18% reporting an overdose in the past three months, with most overdoses related to heroin or nonmedical use of prescription opioids (El-Bassel et al, 2020;Goldenberg, 2020). Although opioid-related overdoses is a major public health problem and may affect many groups of individuals, current knowledge of gendered experiences and requirements in the context of drug overdoses are arguably inadequate (Collins et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Identifying such drivers may thus better guide overdose prevention efforts. Emerging evidence suggests that experiences of violence by intimate partners and non-intimate partners, including police violence, may be contributing to the escalating rates of drug overdose deaths among women (Ataiants et al, 2020;El-Bassel et al, 2020). To our knowledge, however, no studies have examined the effects of different types of violence on non-fatal drug overdose among Black women despite their higher rates of exposures to all types of violence (Breiding et al, 2015;Ritchie, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study of 218 women in harm reduction programs found that higher cumulative scores of lifetime polyvictimization experiences from intimate and non-intimate partners were associated with a higher risk of overdose (Ataiants et al, 2020). Another recent study of 400 sex workers who use drugs in Kazakhstan found that experience of lifetime severe physical violence were associated with greater odds of non-fatal drug overdose (El-Bassel et al, 2020). A study of 624 women who engaged in sex work, the majority of whom identified as Black, found that experiencing police abuse and threats also increased the likelihood of experiencing a non-fatal overdose (Goldenberg et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations